2015
DOI: 10.7567/jjap.55.010301
|View full text |Cite
|
Sign up to set email alerts
|

Observations of multiple stationary striation phenomena in an atmospheric pressure neon plasma jet

Abstract: The formation of multiple stationary striations between a nozzle exit and a conductive target plate was clearly observed at regular intervals using a digital camera along an atmospheric pressure plasma jet of dielectric barrier discharge using a neon gas into ambient air. From the results of measuring using a high-speed camera during the positive current phase, the emission initially started in the middle between the nozzle and the target, and striations progressed in both upward and downward directions. Durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 34 publications
1
11
1
Order By: Relevance
“…In contrast, during the negative voltage period, electrons flow into the target plate. During these periods, the plasma flare is produced between the exit of the plasma equipment and the target; this was already confirmed by Fujiwara et al 24 Figure 5(b) shows the root mean square (RMS) voltage, the RMS current, and the real power as functions of the integration time, and these pa- (1)…”
Section: Resultssupporting
confidence: 68%
“…In contrast, during the negative voltage period, electrons flow into the target plate. During these periods, the plasma flare is produced between the exit of the plasma equipment and the target; this was already confirmed by Fujiwara et al 24 Figure 5(b) shows the root mean square (RMS) voltage, the RMS current, and the real power as functions of the integration time, and these pa- (1)…”
Section: Resultssupporting
confidence: 68%
“…Self-organized striated structures of the plasma emission-established this way-have been observed in CCRF CF 4 plasmas by Phase Resolved Optical Emission Spectroscopy (PROES) and their formation was analyzed and understood by Particle in Cell / Monte Carlo Collision (PIC/MCC) simulations [31]. It is quite obvious that the physical origin of the striations in electronegative CCRF discharges is different from those observed previously in electropositive plasmas [33][34][35][36][37][38][39][40][41][42][43][44][45][46]. For example, one well-known scenario is the striated structure of DC glow discharges, wherein ion-acoustic or ionization waves are considered to be the origin of these features [33][34][35][36].…”
Section: Introductionmentioning
confidence: 97%
“…For example, one well-known scenario is the striated structure of DC glow discharges, wherein ion-acoustic or ionization waves are considered to be the origin of these features [33][34][35][36]. Striations can also occur in inductively coupled plasmas [37][38][39], atmospheric pressure CCRF He H 2 O ⁄ discharges [40], atmospheric pressure plasma jets [41][42][43] , plasma display panels [44], and plasma clouds in the ionosphere [45,46] , etc. In all of these systems, the appearance of striations is associated with the electron kinetics.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the plasma flare shows a stationary plasma striation between the quartz tube and a substrate. 16 These results indicate that the variation of the operating characteristics of the plasma flare is relatively small during the LE-IGCE treatment.…”
Section: Resultsmentioning
confidence: 83%
“…We also developed a specially designed nonthermal atmospheric pressure plasma flare based on DBD. [13][14][15][16] Here, plasma flare is defined as a visible light from the equipment to a target. The utility of the LE-IGCE as a minimally invasive plasma for blood coagulation was experimentally verified.…”
Section: Introductionmentioning
confidence: 99%